Monitoring Floating Solar Tracker Based on Axis Coordinates using LoRa Network - Abyan Arief Fernandez; Andrian Rakhmatsyah; Aulia Arif Wardana (Center of Biomass & Renewable Energy, Diponegoro University, 2020)
This research aimed to build a solar tracker for a floating solar panel and used long–range (LoRa) communication to harvest energy and monitor its process. With the rising demand for renewable energy in these recent years especially for solar energy, it needs to meet this demand to remain relevant for the upcoming years where it will have an even larger impact as we shift into clean energy. Monitoring single–axis solar trackers on rural areas difficult and cost–intensive. The purpose of a floating solar farm is to reduce the cost from buying/renting land. Floating solar panels cannot be monitored using wired because they are moving nodes in the water, it makes wired installation complicated. Hence, using wireless sensornetwork is a solution that allowsremote monitoring of floating solar panels in rural areas and makes moving nodes mentioned above possible. Testing wasperformed by sending 100 packets from the node to its gateway using LoRa modulation, and the gateway successfully received about 90% of the packets sent by the node. The vertical single-axis solar tracker used in floating solar managed to get 17% more energy than the fixed solar with a more stable income for the whole duration of sending 100 packets.